2010
DOI: 10.1074/jbc.m110.141929
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin and Interfacial Microtubule Inhibitors Recognize a Naturally Curved Conformation of Tubulin Dimers

Abstract: Tubulin is able to switch between a straight microtubule-like structure and a curved structure in complex with the stathminlike domain of the RB3 protein (T 2 RB3). GTP hydrolysis following microtubule assembly induces protofilament curvature and disassembly. The conformation of the labile tubulin heterodimers is unknown. One important question is whether free GDP-tubulin dimers are straightened by GTP binding or if GTP-tubulin is also curved and switches into a straight conformation upon assembly. We have obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 66 publications
1
83
0
1
Order By: Relevance
“…Taken together, these observations suggest that stathmin can directly promote catastrophe by binding to and acting upon the exposed protofilaments that are predicted to exist at the tips of growing MTs (9); consideration of the existing stathmin-tubulin complex structures (23)(24)(25)(26) suggests that it acts by inhibiting lateral interactions between the PFs. It is also possible that stathmin increases the GTPase of the tubulin subunits in the protofilaments to which it is bound (27).…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…Taken together, these observations suggest that stathmin can directly promote catastrophe by binding to and acting upon the exposed protofilaments that are predicted to exist at the tips of growing MTs (9); consideration of the existing stathmin-tubulin complex structures (23)(24)(25)(26) suggests that it acts by inhibiting lateral interactions between the PFs. It is also possible that stathmin increases the GTPase of the tubulin subunits in the protofilaments to which it is bound (27).…”
Section: Significancementioning
confidence: 98%
“…Such an inhibition could occur because stathmin's binding site is close to the interface between protofilaments (23-25). Alternatively, because both DL-rings and the T 2 S complex are curved (15)(16)(17)(18)26), stathmin could inhibit lateral interactions by inducing in protofilaments a degree of curvature that is incompatible with their incorporation into the lattice.…”
Section: Significancementioning
confidence: 99%
“…RB3-tubulin includes a longitudinal interaction between tubulin dimers. 18 The similar size of the tau-RB3-tubulin and tau-tubulin complexes indicates that tau is able to mediate these longitudinal tubulin interactions as well (Figure 4). This is in agreement with a recent NMR study which demonstrated longitudinal assembly of tubulin dimers by a tau fragment.…”
mentioning
confidence: 90%
“…Proteins were overexpressed in Escherichia coli BL21 DE3 Star, in LB medium supplemented with kanamycin, using 0.5 mM isopropyl ␤-D-1-thiogalactopyranoside to induce an expression period of 3 h at 37°C. Purification was as described (6) except that a first step of nucleic acid precipitation by spermine (24) was added and that the heating step was omitted for R4 and R4a. The concentration of purified SLD was determined by measuring the absorbance at 280 nm, taking advantage of the presence of tryptophan residues in these constructs, as opposed to wild type RB3 SLD , whose absorbance at 280 nm is very weak.…”
Section: Methodsmentioning
confidence: 99%